Systemic Vascular Function Is Associated with Muscular Power in Older Adults - Kevin S. Heffernan; Angela Chalé; Cynthia Hau; Gregory J. Cloutier; Edward M. Phillips; Patrick Warner; Heather Nickerson; Kieran F. Reid; Jeffrey T. Kuvin; Roger A. Fielding (Journal of Aging Research)
Age-associated loss of muscular strength and muscular power is a critical determinant of loss of physical function and progression to disability in older adults. In this study, we examined the association of systemic vascular function and measures of muscle strength and power in older adults. Measures of vascular endothelial function included brachial artery flow-mediated dilation (FMD) and the pulse wave amplitude reactive hyperemia index (PWA-RHI). Augmentation index (AIx) was taken as a measure of systemic vascular function related to arterial stiffness and wave reflection. Measures of muscular strength included one repetition maximum (1RM) for a bilateral leg press. Peak muscular power was measured during 5 repetitions performed as fast as possible for bilateral leg press at 40% 1RM. Muscular power was associated with brachial FMD (r=0.43, P<0.05), PWA-RHI (r=0.42, P<0.05), and AIx (r=−0.54, P<0.05). Muscular strength was not associated with any measure of vascular function. In conclusion, systemic vascular function is associated with lower-limb muscular power but not muscular strength in older adults. Whether loss of muscular power with aging contributes to systemic vascular deconditioning or vascular dysfunction contributes to decrements in muscular power remains to be determined.